Arctigenin disrupts NLRP3 inflammasome assembly in colonic macrophages via downregulating fatty acid oxidation to prevent colitis-associated cancer. (28th October 2020) - Qiao, Simiao; Lv, Changjun; Tao, Yu; Miao, Yumeng; Zhu, Yanrong; Zhang, Wenjie; Sun, Dandan; Yun, Xinming; Xia, Yufeng; Wei, Zhifeng; Dai, Yue
Abstract: Arctigenin, the major active constituent of Fructus Arctii, has been reported to inhibit the growth of various tumors and alleviate colitis. This study aimed to prove the protective effect of arctigenin on colitis-associated cancer (CAC) and explore its mechanisms. Orally administered arctigenin prevented the progression of colitis and protected against colon carcinogenesis in azoxymethane (AOM)/dextran sulfate sodium (DSS)-induced CAC mice. Arctigenin downregulated NLRP3 inflammasome activation and fatty acid oxidation (FAO) metabolism in macrophages, as determined by untargeted metabolomics. Arctigenin also inhibited the expression of carnitine palmitoyltransferase 1 (CPT1), reduced the acetylation of α-tubulin, and disrupted NLRP3 complex formation, which in turn inactivated the NLRP3 inflammasome. Downregulation of the CPT1-FAO-acetyl-coenzyme A (acetyl-CoA)-acetylated α-tubulin pathway was observed to inhibit the effect of arctigenin on NLRP3 inflammasome assembly, as confirmed by CPT1 overexpression. Lastly, arctigenin was shown to inhibit NLRP3 inflammasome activation and improve CAC in mice, and the effect was significantly diminished by the overexpression of adeno-associated virus (AAV)9-CPT1. Taken together, these results show that the inhibition of NLRP3 inflammasome assembly in macrophages due to FAO downregulation contributes to the preventative effect of arctigenin against CAC. Our findings highlight the potential value of arctigenin to reduce the risk of CAC in patients with colitis. Graphical abstract: Image 1 Highlights: Oral arctigenin can effectively prevent colitis associated cancer (CAC) in mice. Arctigenin selectively downregulates IL-1β expression in the colon of CAC mice. Arctigenin disrupts NLRP3 inflammasome assembly to downregulate IL-1β expression. Arctigenin functions by inhibiting fatty acid oxidation via targeting at CPT1.